Association between both vaginal delivery and cesarean section with epidermoid cervical cancer and precursors. - Fernández Mollinari, Luis (2015)
Introduction: In women with previous traumatic lesions of the uterine cervix human papilloma virus (HPV) may infect cervical epithelium and reach basal and parabasal cells. Objetives: To determine the existence of a stronger relationship between women with vaginal deliveries and cervical squamous cancer and precursors, and women with exclusive cesarean sections. Design: Case-control study. Setting: Hospital Regional Docente de Trujillo, Peru. Participants: Women with clinical and histology diagnosis of cervical cancer and its precursors. Interventions: We included 177 women with clinical and histological diagnosis of cervical cancer or its precursors attended between 2000 and 2002; 197 women without vaginal deliveries or exclusive cesarean section were considered as controls. To determine factors associated with cervical cancer and its precursors we used multivariate analysis and logistic regression. Age, parity, gravity, route of delivery and age at first intercourse were considered as predictor variables. For each of them, the odds ratio was calculated. Statistical significance was found using x2 test. Main Outcome measures: Association between type of delivery and development of cervical cancer. Results: Among variables considered, only age at first intercourse, parity and gravidity, and vaginal delivery were significantly associated with cervical cancer (OR 1,13; CI95% 1,17-24,11, respectively). Women with vaginal delivery had 24 times higher risk to develop cervical cancer in comparison with women who underwent cesarean section only (OR: 24,113, p<0,0000008). Conclusions: Among variables associated with cervical cancer, vaginal delivery was strongly associated and may increase predisposition to develop this neoplasia and its precursors.